Time to reflect is a rare and valued opportunity; a pilot of the NIDUS‐professional dementia training intervention for homecare workers during the Covid‐19 pandemic. (6th February 2022) - Kelleher, Daniel; Lord, Kathryn; Duffy, Larisa; Rapaport, Penny; Barber, Julie; Manthorpe, Jill; Leverton, Monica; Dow, Briony; Budgett, Jessica; Banks, Sara; Duggan, Sandra; Cooper, Claudia
Abstract: Most people living with dementia want to continue living in their own home for as long as possible and many rely on support from homecare services to do so. There are concerns that homecare often fails to meet the needs of clients with dementia, but there is limited evidence regarding effective interventions to improve its delivery for this client group. We aimed to assess whether a co‐designed, 6‐session dementia training intervention for homecare workers (NIDUS‐professional) was acceptable and feasible. Facilitated training sessions were delivered over 3 months, followed by 3, monthly implementation meetings to embed changes in practice. Two trained and supervised facilitators without clinical qualifications delivered the intervention via group video‐calls during Oct 2020–March 2021 to a group of seven homecare workers from one agency in England. Participants provided qualitative feedback 3‐ and 6‐months post intervention. Qualitative interview data and facilitator notes were integrated in a thematic analysis. Adherence to the intervention and fidelity of delivery were high, indicating that it was acceptable and feasible to deliver in practice. Thirty of a possible 42 (71.4%) group sessions were attended. In our thematic analysis we report one over‐arching theme: ' Having time and space to reflect is a rare opportunity' . Within this we identified four subthemes (Having time to reflect is a rare opportunity; Reflecting with peers enhances learning; Reflection and perspective taking can improve care; Recognising skills and building confidence) through which we explored how participants valued the intervention to discuss their work and learn new skills. Attendance was lower for the implementation sessions, perhaps reflecting participants' lack of clarity about their purpose. We used our findings to consider how we can maintain positive impacts of the manualised sessions, so that these are translated into tangible, scalable benefits for people living with dementia and the homecare workforce. A randomised feasibility trial is underway.